1994
DOI: 10.1042/bj2980207
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic ketogenesis in newborn pigs is limited by low mitochondrial 3-hydroxy-3-methylglutaryl-CoA synthase activity

Abstract: In newborn-pig hepatocytes, the rate of oleate oxidation is extremely low, despite a very low malonyl-CoA concentration. By contrast, the sensitivity of carnitine palmitoyltransferase (CPT) I to malonyl-CoA inhibition is high, as suggested by the very low concentration of malonyl-CoA required for 50% inhibition of CPT I (IC50). The rates of oleate oxidation and ketogenesis are respectively 70 and 80% lower in mitochondria isolated from newborn-pig liver than from starved-adult-rat liver mitochondria. Using pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
2
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 37 publications
2
29
2
1
Order By: Relevance
“…No significant interaction was found. As expected, BHB production was low as it is known that ketogenic capacity of liver from newborn pigs is much lower than in other mammalian species (Duée et al, 1994) and low ketone production persists in the adult pig (Duée et al, 1994). BHB levels in the present study were in the lower range to previously reported values for hepatocytes isolated from 60 kg pigs (Fernández-Fígares et al, 2004).…”
Section: Bhb Synthesiscontrasting
confidence: 50%
“…No significant interaction was found. As expected, BHB production was low as it is known that ketogenic capacity of liver from newborn pigs is much lower than in other mammalian species (Duée et al, 1994) and low ketone production persists in the adult pig (Duée et al, 1994). BHB levels in the present study were in the lower range to previously reported values for hepatocytes isolated from 60 kg pigs (Fernández-Fígares et al, 2004).…”
Section: Bhb Synthesiscontrasting
confidence: 50%
“…Fatty acids constitute about 60% of the total energy in porcine milk, and neonates rely heavily on fatty acids for survival [1]. Because piglets seem to have a limited mitochondrial P-oxidation of longchain fatty acids [3][4][5]20], a relatively large contribution of peroxisomal P-oxidation may act as a compensatory mechanism to use milk-derived fatty acids, which in porcine milk are almost exclusively long-chain fatty acids [25],…”
Section: ß-Oxidation In Piglet Livermentioning
confidence: 99%
“…Ketogenesis from fatty acids is a normal com ponent of the adaptations in neonates of rats and many other species [1], Recent evidence [2][3][4][5] from research using a variety of experi mental approaches has indicated that piglets have a limited ketogenic capacity relative to the adult rat which has been the most widely studied model. Because the mortality of pig lets and other neonates remains a major prob lem, an increased understanding of the meta bolic adaptations that occur after birth is im portant.…”
mentioning
confidence: 99%
“…The attenuated activity of mHMGCS appears not to be associated with a low mRNA abundance but rather a low rate of translation (5). The physiological significance of the unique structure of hepatic CPT I is not known, but it was suggested that fatty acid oxidation in mitochondria may be limited in neonatal pigs due to the diminished ketogenic pathway (8). This prompted us to investigate the oxidation occurring in peroxisomes (which is usually considered an ancillary oxidative pathway to mitochondria oxidation), because acetate is reported to be the primary product of peroxisomal ␤-oxidation (18) due to the high level of short-chain acyl-CoA thioesterase (39).…”
mentioning
confidence: 99%
“…The porcine CPT I protein is a natural chimera of the more typical mammalian liver (L) and muscle (M)-CPT I isotypes, containing the L-CPT I binding site for acyl-CoA and the M-CPT I binding sites for carnitine and malonyl-CoA. Besides the unique structure of porcine CPT I, the activity of mitochondrial 3-hydroxy-3-methylglutaryl-coenzyme A synthase (mHMGCS), the key enzyme regulating ketogenesis, is extremely low in suckling piglets, which results in the reduced ketogenesis (8). The attenuated activity of mHMGCS appears not to be associated with a low mRNA abundance but rather a low rate of translation (5).…”
mentioning
confidence: 99%